Effective marketing of ecological resource-saving technologies at food enterprises - Naumenko, O. P.; Naumenko, M. O.; Naumenko, O. O.; Chupryna, N. M.; Chernysheva, O. M.; Fedorenko, I. A. (Український державний хіміко-технологічний університет, 2022)
strike», which in the shortlist competed with «climate emergency», «climate crisis», «ecoanxiety». Climate change of the decade is considered a real shock not only to Ukraine but to the world as a whole. The United Nations World Food Program, the world’s largest humanitarian organization, has been awarded the Nobel Peace Prize for its project «Foodis the best vaccine against chaos.» However, world food prices in 2021 increased by 32.8%. There are many reasons for the promotion of inflation: drought; high demand for grain crops in China; Russia’s export restrictions; rising oil prices; closed borders and outflow of labor. In 2022, the agricultural sector will face new challenges: higher prices for fertilizers (70… 300%) and maritime transport (300… 500%); energy crisis; inflated demand and political constraints; climate change. Given the trends of climate change, the author’s team considers it appropriate to choose as the object of study one of the most waterintensive in cultivation and in demand in the use of vegetable crops – carrots, considering it as a «living model». A fairly thick cover layer contains a lot of nutrients, but too little fiber, which with the existing means of mechanized harvesting and processing injures and damages up to 40% of roots. With significant resources for growing, harvesting and storage, up to 25% of the crop is lost. Carrots are the most difficult crop to store. Thus, the development of the concept of «Ñonvenient food» involves not only the intensification and revision of existing functions, but also to change the perception of the organization of technological processes, which will: save drinking water when washing roots by attracting some squeezed liquid; to preserve useful properties due to timely warm processing; avoid the above restrictions on the production and consumption of natural juice. The relatively high hardness of carrots limits the economic feasibility. Under the current circumstances, sufficient favorable conditions have not yet been created for the development and implementation of innovations.
Ефективний маркетинг ресурсозберігаючих екологічних технологій на харчових підприємствах
Keywords: convenient food; saving of resources; useful properties; carrot powder; зручна їжа; економіка ресурсів; корисні властивості; моркв'яний порошок